PRELIMINARY STUDY ON ADMINISTRATIVE MODEL OF PROFESSIONAL LEARNING COMMUNITY TO DEVELOP THAI LANGUAGE TEACHING CAPACITY OF PRIMARY SCHOOL TEACHERS IN THREE SOUTHERN BORDER PROVINCES - Khanom, Sutiporn; Daungkaew, Ratana; Ngudgratoke, Sungworn; Numun, Wanna (PEOPLE: International Journal of Social Sciences, 2017)
The three southern border provinces of Thailand are unique with their own language and cultural identity. Most students speak Thai as a second language. Such conditions, educators put their effort seeking appropriate methods of teaching Thai language to the context of those areas. This research aims to develop the administrative model of professional learning communities to improve teaching skills of elementary school teachers in the three southern border provinces. The study was guided by two main questions: (1) what are the components of the PLC administrative model?; and (2) how should the model be developed in improving Thai teachers’ teaching ability? A mixed-methods approach was employed, which consists of document analyses to identify the elements of the PLC administrative model, and then to synthesize the preliminary model. After that the researcher examined the suitability and feasibility of the model by using in-depth interviews with 17 key informants; focus group with 20 experts; and questionnaires with 705 school administrators and Thai language teachers from elementary schools in those three southern border provinces. Research data were analyzed using frequency, percentage, mean, standard deviation, and content analysis. The preliminary results revealed that the PLC administrative model for the development of Thai language teachers’ teaching skills in those areas should comprise four main stages: (1) planning for establishing the objectives of a collaborative team and guidelines for action; (2) implementing the action plan into classroom practices along with teachers’ shared learning and experiences, (3) investigating the performances of teachers by using methods of supervision, monitoring, and evaluation, and 4) rectifying all practices to improve the model for the sustainable development of Thai language teachers in the three southern border provinces. The results suggest that each stage of the effective model should be interrelated to the PLC principle. For better conclusion, the model is further experimented within two participative schools.